Die pastorale gesprek binne 'n narratiewe diakonale pastoraat - PR van Heerden; DJ Kotzé (Acta Theologica)
The person and the problem often becomes so intertwined that people's lives and relationships are constituted by their problems. This article focuses on this issue from a narrative approach. The purpose is to externalise the problem and in this way to separate the person from the problem. The process of pastoral therapy explores the disempowering effect of the problem as a dominant story shaping a person's life. This is followed by an exploration of alternative stories that may be indicative of a more preferred life. Criticism that may arise from a Biblical perspective is attended to. Ways in which such an approach can draw on the new life through Christ and the grace of God in people's lives, even those who do not believe in Him, are integrated into this approach.